Challenges and opportunities of telehealth digital equity to manage HIV and comorbidities for older persons living with HIV in New York State - Abigail Baim-Lance; Matthew Angulo; Mary Ann Chiasson; Helen-Maria Lekas; Rachel Schenkel; Jason Villarreal; Anyelina Cantos; Christine Kerr; Aarthi Nagaraja; Michael T. Yin; Peter Gordon (BMC, 2022)
Abstract Background Older persons living with HIV (PLWH) need routine healthcare to manage HIV and other comorbidities. This mixed methods study investigated digital equity, constituted as access, use and quality, of HIV and specialty telehealth services for PLWH > 50 years during the initial wave of the COVID-19 pandemic when services transitioned to remote care. Methods A survey of closed and open-ended questions was administered to 80 English (N = 63) and Spanish (N = 17) speaking PLWH receiving HIV care at an Academic Medical Center (N = 50) or a Federally Qualified Health Center (N = 30) in New York State. Quantitative analyses examined characteristics predicting telehealth use and visit quality. Qualitative analyses utilized thematic coding to reveal common experiences. Results were integrated to deepen the interpretation. Results Telehealth access and use were shaped by multiple related and unstable factors including devices and connectivity, technology literacy, and comfort including privacy concerns. Participants demonstrated their substantial effort to achieve the visit. The majority of patients with a telehealth visit perceived it as worse than an in-person visit by describing it as less interpersonal, and resulting in poorer outcomes, particularly participants with less formal education. Technology was not only a barrier to access, but also influenced perceptions of quality. Conclusions In the COVID-19 pandemic initial wave, barriers to using telehealth were unequally distributed to those with more significant access and use challenges. Beyond these barriers, examining the components of equity indicate further challenges replicating in-person care using telehealth formats for older PLWH. Work remains to establish telehealth as both equitable and desirable for this population.